2021
DOI: 10.1097/md.0000000000026202
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of platelet-to-lymphocyte ratio in neoadjuvant chemotherapy for solid tumors

Abstract: Introduction: Previous research indicates that the platelet-to-lymphocyte ratio (PLR) may be an indicator of poor prognosis in many tumor types. However, the PLR is rarely described in patients undergoing neoadjuvant chemotherapy (NAC) for solid tumors. Thus, we performed a meta-analysis to investigate the prognostic value of this ratio for patients with solid tumors treated by NAC.Methods: A comprehensive search of the literature was conducted using the PubMed, EMBASE, Cochrane Library, and Web of Science dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…A meta-analysis by Long et al . 63 suggested that a lower PLR was associated with an increased likelihood of a pCR, in combined analysis of breast and rectal tumours. This is the first systematic review to investigate the role of the PLR in predicting a pCR, specifically in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Long et al . 63 suggested that a lower PLR was associated with an increased likelihood of a pCR, in combined analysis of breast and rectal tumours. This is the first systematic review to investigate the role of the PLR in predicting a pCR, specifically in breast cancer.…”
Section: Discussionmentioning
confidence: 99%